The role of gender-specific factors in the choice of specialty training in obstetrics and gynecology: results from a survey among medical students in Germany - Riedel, Maximilian; Hennigs, André; Dobberkau, Anna Maria; Riedel, Caroline; Bugaj, Till Johannes; Nikendei, Christoph; Amann, Niklas; Karge, Anne; Eisenkolb, Gabriel; Tensil, Maria; Recker, Florian; Riedel, Fabian (Archives of gynecology and obstetrics, 2022)
The field of obstetrics and gynecology (OB/GYN) is facing growing competition for young professionals in Germany, with high interest rates among female graduates and a declining proportion of male students who choose residency training in the field. The aim of this study is to analyze general and gender-dependent factors that influence the decision for or against specialty training in OB/GYN among medical students in Germany.
Gesehen am 07.08.2023